2016
DOI: 10.1039/c6ra01926a
|View full text |Cite
|
Sign up to set email alerts
|

Dealloyed PdAg core Pt monolayer shell electrocatalyst for oxygen reduction reaction

Abstract: A core–shell nanostructure with dealloyed PdAg nanoparticles as the core and a Pt monolayer as the shell shows much higher catalytic properties for oxygen reduction reaction as compared with its counterpart with alloyed PdAg as the core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…For a comparison, the results of Fe 0.5 NC‐900‐1 and Fe 2.5 NC‐900‐3 are also calculated, as shown in Figure S6. For all of the catalysts, the numbers of electron transfer of ORR are close to four, indicating that the ORR on the catalysts is a typical four electron reaction process of direct reduction of oxygen molecules to water in alkaline environment …”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…For a comparison, the results of Fe 0.5 NC‐900‐1 and Fe 2.5 NC‐900‐3 are also calculated, as shown in Figure S6. For all of the catalysts, the numbers of electron transfer of ORR are close to four, indicating that the ORR on the catalysts is a typical four electron reaction process of direct reduction of oxygen molecules to water in alkaline environment …”
Section: Resultsmentioning
confidence: 84%
“…For all of the catalysts, the numbers of electron transfer of ORR are close to four, indicating that the ORR on the catalysts is a typical four electron reaction process of direct reduction of oxygen molecules to water in alkaline environment. 42 The stability of the electrocatalysts is as an important indicator for evaluating the catalytic performance. 25 Figure 5A and 5B give the comparison of the first and the 1000th CV curves of Fe 1.5 NC-900-2 and commercial Pt/C catalysts in O 2 -saturated 0.1 M KOH electrolyte, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Pt alloy catalysts show excellent durability. These favorable phenomena are usually ascribed to the dealloying of the 3d transition non-noble metals such as Ni. , This selective dissolution results in variation in the nanoparticle structure; i.e., a Pt-rich shell covering a Pt alloy core is formed. Rudi et al also reported a systematic study on the enhancement of ORR activity by varying the Ni amount in the catalysts of the Pt x Ni 1– x series .…”
Section: Introductionmentioning
confidence: 99%